Increasing the innovation potential of construction materials industry enterprises - Kurbanova, Shaxnoza (GREEN ECONOMY AND DEVELOPMENT, 2024)
The construction materials industry in Uzbekistan plays a crucial role in supporting the nation's infrastructure growth and economic development. However, to meet the increasing demands of modernization and sustainable development, there is a need to enhance the innovation potential of enterprises within this sector. This article explores the current state of the construction materials industry in Uzbekistan, identifying key challenges and opportunities for innovation. By analyzing factors such as technological advancement, regulatory environment, and resource utilization, the study proposes strategies to foster innovation, including the adoption of digital technologies, investment in research and development (R&D), and collaboration between private and public sectors. The findings suggest that with targeted support and policy reform, Uzbek enterprises in the construction materials industry can increase their competitiveness, improve efficiency, and contribute to sustainable development goals. This study provides a framework that can be applied to similar emerging markets seeking to enhance innovation in the construction sector.